KOSMOS 2017 Peru mesocosm study: Gut fluorescence and C/N ratio of Paracalanus sp. - Silke Lischka; Patricia Ayón; Elda Luz Pinedo Arteaga; Anna Schukat; Jan Taucher; Rainer Kiko; Helena Hauss; Sabrina Dorschner; Wilhelm Hagen; Mariona Segura-Noguera (PANGAEA, 2023)
Gut fluorescence and C/N ratio of Paracalanus sp. determined during two occassions during the mesocosm experiment (Sampling Day 21/22 and 34/35).
In: Lischka, S et al. (2022): Response of zooplankton community succession and trophic links to simulated upwelling conditions during a mesocosm experiment in the coastal upwelling off Callao Bay (Peru) in austral summer 2017 (KOSMOS 2017 Peru mesocosm study) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.947833